Conserved white-rot enzymatic mechanism for wood decay in the Basidiomycota genus Pycnoporus. (12th June 2020) - Miyauchi, Shingo; Hage, Hayat; Drula, Elodie; Lesage-Meessen, Laurence; Berrin, Jean-Guy; Navarro, David; Favel, Anne; Chaduli, Delphine; Grisel, Sacha; Haon, Mireille; Piumi, François; Levasseur, Anthony; et al.
Abstract: White-rot (WR) fungi are pivotal decomposers of dead organic matter in forest ecosystems and typically use a large array of hydrolytic and oxidative enzymes to deconstruct lignocellulose. However, the extent of lignin and cellulose degradation may vary between species and wood type. Here, we combined comparative genomics, transcriptomics and secretome proteomics to identify conserved enzymatic signatures at the onset of wood-decaying activity within the Basidiomycota genus Pycnoporus . We observed a strong conservation in the genome structures and the repertoires of protein-coding genes across the four Pycnoporus species described to date, despite the species having distinct geographic distributions. We further analysed the early response of P. cinnabarinus, P. coccineus and P. sanguineus to diverse (ligno)-cellulosic substrates. We identified a conserved set of enzymes mobilized by the three species for breaking down cellulose, hemicellulose and pectin. The co-occurrence in the exo-proteomes of H2 O2 -producing enzymes with H2 O2 -consuming enzymes was a common feature of the three species, although each enzymatic partner displayed independent transcriptional regulation. Finally, cellobiose dehydrogenase-coding genes were systematically co-regulated with at least one AA9 lytic polysaccharide monooxygenase gene, indicative of enzymatic synergy in vivo . This study highlights a conserved core white-rot fungal enzymatic mechanism behind the wood-decaying process.